Laparoscopic approach to vesicovaginal fistulae. (January 2019) - Ramphal, S.R.
Abstract: The surgical repair of vesicovaginal fistula (VVF) over the last two decades has evolved from the transabdominal/transvaginal route to minimally invasive techniques of laparoscopy and robotic surgery. The indications for laparoscopic repair include supratrigonal fistulae, and stenotic/narrow vaginas that make vaginal access to the fistula site difficult. In the current published literature, comparable results have been reported with open surgery. The initial techniques were performed to simulate the open classic technique described by O'Conor, but with better imaging, exposure and magnification, the modified O'Conor (smaller cystotomy) and the extravesical approaches (no cystotomy) are being performed with comparable results. Difficulties such as depth perception, suturing and ergonomics together with the steep learning curve associated with laparoscopy have been overcome with the introduction of robotics. Reports on laparoendoscopic single site surgery (LESS) and transvesicoscopic VVF repairs with successful outcomes have been published, but studies on a large number of patients are needed to establish their effectiveness. Difficulties of managing suturing have been circumvented with the usage of the barbed suture; however, more data are required to establish its efficacy. Although the laparoscopic/robotic approach of a VVF repair offers numerous advantages, the best chance of success is achieved with the first surgical attempt using an approach that the surgeon is familiiar in performing. Highlights: The surgical repair of vesicovaginal fistula (VVF) over the last two decades has evolved. Indications for laparoscopic repair include supratrigonal fistulae and stenotic/narrow vaginas. Depth perception, suturing and ergonomics are achieved with robotics. Transvesicoscopic VVF repairs with successful outcomes have been reported. An approach that the surgeon knows how best to perform is critical.